Metabolic syndrome and dyslipidemia in xanthelasma palpebrarum and associated risk–2 factors–A case‐control study. (30th September 2022) - Agarwal, Komal; Saikia, Padmaja; Podder, Indrashis
Abstract: Abstract Background: Xanthelasma palpebrarum (XP) primarily causes cosmetic disfigurement. However, systemic associations like metabolic syndrome (MetS) and dyslipidemia need consideration. Objective: Determining the prevalence of MetS and dyslipidemia in XP patients and explore risk factors. Methods: Our case–control study included 106 XP patients(cases) and 106 age‐and‐sex matched healthy controls. All subjects underwent detailed history taking, physical examination, and biochemical investigations. MetS and obesity were diagnosed by NCEP‐ATP III criteria and modified BMI classification for Asian‐Indians, respectively. Results: The odds ratio (OR) and 95% CI for XP patients vs. non‐XP controls were 1.6 (95% CI 0.8–3.2, p = 0.1) for MetS, 1.4 (95% CI 0.6–3.1, p = 0.4) for dyslipidemia and 0.2 (95% CI 0.07–0.4, p < 0.0001) for overweight/obesity. Extensive disease, DM, and low serum HDL‐C were significantly associated with MetS in XP patients (vs. controls). Normal waist circumference (AOR 21.3, 95% CI 3.5–127.6, p = 0.0008), normal blood glucose (AOR 21.4, 95% CI 3.1–145.1, p = 0.002), and normal blood pressure (AOR 22.3, 95% CI 3.9–124.9, p = 0.0004) significantly reduced the risk of MetS, while bilateral ocular involvement (AOR 4.3, 95% CI 1.1–18.7, p = 0.04) significantly increased the risk of dyslipidemia in XP patients. Conclusion: Xanthelasma palpebrarum patients are more prone to develop MetS and dyslipidemia and need evaluation, despite being a primarily cosmetic concern. Extensive disease and bilateral ocular involvement are significant risk factors. Adequate counseling and healthy life‐style measures are crucial to minimize systemic complications.